2023
DOI: 10.30574/gscbps.2023.22.1.0502
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and nutritional characterization of flours from cashew apple, Kent mango peelings and kernel almonds collected in Korhogo city (Northern Ivory Coast

Abstract: Present study aims to valorize agricultural by-products which are cashew apple, Kent mango peelings and kernel almonds from Korhogo (Northern Côte d’Ivoire). After sampling, sun-drying and milling of these by-products, the physicochemical and nutritional parameters of flours obtained were determined with focused on food use. For physicochemical properties, moisture contents are respectively 25.33±0.33%, 5.44±0.19% and 14.55±0.19% with dried cashew apple, mango almonds and peelings. pH values are respectively 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…These values have widely increased to an outstanding record. For instance, in 2022 alone, 1,028,172 tons of cashew nuts were recorded and [21] have shown that cashew apples account for 9 to 10 times the weight of nuts. This means that about 9 to 10 million tons of cashew apples have been generated.…”
Section: The Potential Of Crops Residues In Côte D'ivoirementioning
confidence: 99%
“…These values have widely increased to an outstanding record. For instance, in 2022 alone, 1,028,172 tons of cashew nuts were recorded and [21] have shown that cashew apples account for 9 to 10 times the weight of nuts. This means that about 9 to 10 million tons of cashew apples have been generated.…”
Section: The Potential Of Crops Residues In Côte D'ivoirementioning
confidence: 99%